2014
DOI: 10.1063/1.4901999
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization reversal behavior in complex shaped Co nanowires: A nanomagnet morphology optimization

Abstract: A systematic micromagnetic study of the morphological characteristic effects over the magnetic static properties of Co-based complex shaped nanowires is presented. The relevance of each characteristic size (i.e. length L, diameter d, and size of the nanowires head T ) and their critical values are discussed in the coercive field optimization goal. Our results strongly confirms that once the aspect ratio ( L d ) of the nanowire is bigger than around 10, the length is no more the pertinent parameter and instead … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
2
17
0
2
Order By: Relevance
“…This result has been validated by simulations of the reversal mechanism of various shapes (i.e. ellipsoid, cylinder, diabolo and dumbbell) and they yielded a critical ratio [27] showing that the maximum coercive value is constant for the longest nanowires and start to decrease for L d ≤ 15 (10% loss is observed in Figure 3 at L d = 15 ).…”
Section: Nanowire Shape and Length Effectsmentioning
confidence: 60%
See 4 more Smart Citations
“…This result has been validated by simulations of the reversal mechanism of various shapes (i.e. ellipsoid, cylinder, diabolo and dumbbell) and they yielded a critical ratio [27] showing that the maximum coercive value is constant for the longest nanowires and start to decrease for L d ≤ 15 (10% loss is observed in Figure 3 at L d = 15 ).…”
Section: Nanowire Shape and Length Effectsmentioning
confidence: 60%
“…Micromagnetic simulations performed on one-dimensional nano-objects of different shapes showed that the magnetization reversal is strongly dependent of the length over diameter ratio L d (author?) [26,27]. From these previous works, the coercive values in one-dimensional systems are expected to increase with the increasing ratio for a very large range of length and diameter size.…”
Section: Nanowire Shape and Length Effectsmentioning
confidence: 99%
See 3 more Smart Citations